Economic evaluation of an e-mental health intervention for patients with retinal exudative diseases who receive intraocular anti-VEGF injections (E-PsEYE): protocol for a randomised controlled trial. Issue 11 (15th November 2017) - van der Aa, Hilde P A; van Rens, Ger H M B; Verbraak, Frank D; Bosscha, Machteld; Koopmanschap, Marc A; Comijs, Hannie C; Cuijpers, Pim; van Nispen, Ruth M A
Abstract : Introduction: Because of the great potential of vascular endothelial growth factor inhibitors (anti-VEGF) for retinal exudative diseases, an increased number of patients receives this treatment. However, during this treatment, patients are subjected to frequent invasive intravitreal injections, and the effects on reversing the process of vision loss are uncertain, which may have negative consequences for patients' mental health. One in three patients experience at least mild symptoms of depression/anxiety. To support patients in dealing with these symptoms, an e-mental health intervention (called E-PsEYE) has been developed. E-PsEYE is based on cognitive–behavioural therapy (CBT) and contains nine modules. A stepped-care model with three steps will be used to deliver the intervention: (1) providing information and psychoeducation, (2) when symptoms of depression/anxiety persist, guided CBT is offered and supported by social workers from low vision rehabilitation services and (3) when symptoms still persist, patients are referred to their general practitioner. Methods and analysis: An economic evaluation from a healthcare and societal perspective will be conducted alongside a multicentre randomised controlled trial in two parallel groups to evaluate whether E-PsEYE is cost-effective in comparison with usual care. Participants (n=174) will be 50 years or older, have retinal exudative diseases, receive anti-VEGF treatment and have mild symptoms of depression/anxiety (assessed prior to randomisation). Main outcome measures are: depression (Patient Health Questionnaire-9), anxiety (Hospital Anxiety and Depression Scale-Anxiety) and quality-adjusted life-years (determined with the Health Utility Index-3 and the EuroQol-5 dimensions). Five measurements take place: at baseline and after 3, 6, 9 and 12 months. Ethics and dissemination: The study has been approved by the Medical Ethics Committee of the VU University Medical Centre Amsterdam. It will provide new and essential information on the cost-effectiveness of an innovative intervention for a vulnerable population. Outcomes will be disseminated through peer-reviewed publications and conference presentations. Trial registration: http://www.trialregister.nl, identifier: NTR6337.